2022
DOI: 10.3389/fnmol.2022.1013033
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of ethyl pyruvate in spinal cord injury by inhibiting the high mobility group box-1/toll-like receptor4/nuclear factor-kappa B signaling pathway

Abstract: Spinal cord injury (SCI) is a high incident rate of central nervous system disease that usually causes paralysis below the injured level. The occurrence of chronic inflammation with the axonal regeneration difficulties are the underlying barriers for the recovery of SCI patients. Current studies have paid attention to controlling the instigative and developmental process of neuro-inflammation. Ethyl pyruvate, as a derivative of pyruvate, has strong anti-inflammatory and neuroprotective functions. Herein, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Janus kinase (JAK) / signal transducer, activator of transcription (STAT)1 as well as nuclear factor-κB (NF-κB) signaling pathways are key promoters of the in ammation in DKD, which are involved in expression of pro-in ammatory molecules, including interleukin-1 (IL-1), IL-6, and tumor necrosis factor-α (TNF)-α 6,7 . Wherein, activation of both STAT1 and NF-κB are closely related to toll like receptors (TLRs), which are overexpressed in DKD renal tissue, with TLR4 playing a crucial role in persistent in ammation [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Janus kinase (JAK) / signal transducer, activator of transcription (STAT)1 as well as nuclear factor-κB (NF-κB) signaling pathways are key promoters of the in ammation in DKD, which are involved in expression of pro-in ammatory molecules, including interleukin-1 (IL-1), IL-6, and tumor necrosis factor-α (TNF)-α 6,7 . Wherein, activation of both STAT1 and NF-κB are closely related to toll like receptors (TLRs), which are overexpressed in DKD renal tissue, with TLR4 playing a crucial role in persistent in ammation [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…For example,Feng et al showed that overexpression of miR-204 suppressed the inflammatory response in SCI mice(Feng et al, 2019).Wan et al found that miR-129-5p alleviated SCI in mice by inhibiting apoptosis and inflammatory response through the high mobility group protein 1 (HMGB1)/TLR4/NF-κB pathway(Wan et al, 2020). HMGB1 is an upstream factor in the inflammatory response, activating canonical inflammatory pathways such as NF-κB and MAPK triggering glial cell activation and inflammatory response after SCI(Fan et al, 2022). Several studies have shown that inhibition of the inflammatory response by inhibiting HMGB1 activity ameliorates spinal cord edema and injury.…”
mentioning
confidence: 99%